Oxygen-incorporated MoX (X: S, Se or P) nanosheets via universal and controlled electrochemical anodic activation for enhanced hydrogen evolution activity. (August 2019) - Deng, Yunqie; Liu, Zhen; Wang, Aizhu; Sun, Dehui; Chen, Yuke; Yang, Linjing; Pang, Jinbo; Li, Hai; Li, Haidong; Liu, Hong; Zhou, Weijia
Abstract: Molybdenum disulphide (MoS2 ) presents a promising electrocatalyst for hydrogen evolution reaction (HER). Immense effort has been made to optimize MoS2 catalysts with more active sites for the sake of satisfying HER performance. In this work, the MoS2 is modulated by electrochemical anodic activation at positive potentials in acidic media to fast intercalate oxygen into MoS2 in 200 s, leading to the dramatic enhancement for HER activity. Cyclic voltammetry, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, in situ atomic force microscope and operando Raman spectroscopy are applied to explore the oxygen doping process of MoS2 in 0.5 M H2 SO4 electrolyte. In brief, the optimal oxygen doped MoS2 catalyst exhibits an onset potential of as low as −87 mV vs. RHE at 1 mA cm −2 accompanied by excellent stability, which is reduced about 50 mV compared to that before electrochemical anodic activation of MoS2 (135 mV). This work will create a simple and universal method to improve the activities of catalysts by electrochemical anodic activation process, which was successfully applied to MoS2, MoSe2 and MoP. Graphical abstract: Image 1 Highlights: Oxygen incorporation by electrochemical anodic activation process was put forward for the first time. The process of oxygen incorporation is quite fast, simple and controllable by anodic cyclic voltammetry scan. The anodic activation is a universal method for molybdenum compounds of MoS2, MoSe2 and MoP to enhance HER activities.